ERROR ANALYSIS ON LEARNING TENSES IN TRANSFORMING DIRECT INTO INDIRECT SPEECH BY THE SECOND YEAR STUDENTS OF SMK 1 BOYOLALI - TAUFANAWATI , EMI (2007)
This study aims to know the achievements of the students in doing test, to know the kinds of direct indirect speech error and to find the most dominant type of error and to know the source of direct and indirect speech errors. The result of this study is intended to give two positive contributions to teaching and learning English. The type of this study is descriptive qualitative method. To analyze the data, the writer uses the surface strategy taxonomy . It means that the writer classifying the errors based on their type of errors. The result of the research shows that (1) the achievement of the students in doing test is fair. (2) The types of direct and indirect speech errors done by the students are addition, omission, misorde ring and misformation. After analyze the data, the writer finds that the number of errors are 51 sentences, consist 7 error of omission sentences, 5 error of addition sentences, 2 error of misordering sentences and 37 error of misformation. (3) The most dominant type of error made by the students is misformation error. (4) The sources of error done by the students are intralingual transfer and interlingual transfer.